An active DNA-based nanoprobe for photoacoustic pH imaging. Issue 72 (23rd August 2018) - Baumann, Kevin N.; Fux, Alexandra C.; Joseph, James; Bohndiek, Sarah E.; Hernández-Ainsa, Silvia
Abstract : A DNA-based nanoprobe sensitive to pH has been developed for pH photoacoustics imaging through a ratiometric approach. Abstract : We report an active DNA construct capable of probing pH through a photoacoustic (PA) ratiometric analysis approach. Our nanoprobe enables different PA readout in tissue mimicking phantoms in the range between pH 6.8 to 7.8 at physiologically relevant sodium concentrations. Thus, it represents a promising platform to probe pH values relevant to the tumor microenvironment using PA.